Progesterone Activates Multiple Innate Immune Pathways in Chlamydia trachomatis‐Infected Endocervical Cells. (11th November 2013) - Wan, Charles; Latter, Joanna L.; Amirshahi, Ashkan; Symonds, Ian; Finnie, Jane; Bowden, Nikola; Scott, Rodney J.; Cunningham, Kelly A.; Timms, Peter; Beagley, Kenneth W.
<x xml:space="preserve">Abstract</x> Problem Susceptibility to Chlamydia trachomatis infection is increased by oral contraceptives and modulated by sex hormones. We therefore sought to determine the effects of female sex hormones on the innate immune response to C. trachomatis infection. Method of study ECC‐1 endometrial cells, pre‐treated with oestradiol or progesterone, were infected with C. trachomatis and the host transcriptome analysed by Illumina Sentrix HumanRef‐8 microarray. Primary endocervical epithelial cells, prepared at either the proliferative or secretory phase of the menstrual cycle, were infected with C. trachomatis and cytokine gene expression determined by quantitative RT‐PCR analysis. Results Chlamydia trachomatis yield from progesterone‐primed ECC‐1 cells was significantly reduced compared with oestradiol‐treated cells. Genes upregulated in progesterone‐treated and Chlamydia‐infected cells only included multiple CC and CXC chemokines, IL‐17C, IL‐29, IL‐32, TNF‐α, DEFB4B, LCN2, S100A7‐9, ITGAM, NOD2, JAK1, IL‐6ST, type I and II interferon receptors, numerous interferon‐stimulated genes and STAT6. CXCL10, CXCL11, CX3CL1 and IL‐17C, which were also upregulated in infected secretory‐stage primary cells, and there was a trend towards higher levels of immune mediators in infected secretory‐phase compared with proliferative‐phase cells. Conclusion Progesterone treatment primes multiple innate immune pathways in hormone‐responsive epithelial cells that could potentially increase resistance to chlamydial infection.